Salmonella osteomyelitis of unknown origin: an underestimated infection - Victor Rentmeister; Noel Lorenzo-Villalba; Yilmaz Gorur; Michele Yerna; Deeba Ali (European Journal of Case Reports in Internal Medicine, 2023)
Salmonella osteomyelitis is an underdiagnosed pathology with unusual clinical presentations. The patient was a 24-year-old female with no previous medical history who presented to the emergency department with progressive pain in the left arm for several months. She was initially treated unsuccessful with augmentin for 7 days for suspicious cellulites. Standard elbow X-rays described a lesion initially considered as metastatic. Investigations were completed with magnetic resonance imaging (MRI) compatible with osteomyelitis. Following surgical sampling, salmonella enterica infection was diagnosed. The patient recovered full use of her limb after 8 days of IV antibiotic therapy with third-generation cephalosporin, and she completed 11 weeks of antibiogram-targeted PO fluoroquinolone therapy. Salmonella osteomyelitis could mimic other diseases, making diagnosis difficult.